Investigation of the radial bearing force developed during actual ship operations. Part 2: Unsteady maneuvers. (15th September 2015) - Ortolani, Fabrizio; Mauro, Salvatore; Dubbioso, Giulio
Abstract: The bearing radial load developed by a propeller during actual ship operating conditions is thoroughly investigated by means of a free running, self-propelled twin screw model at the CNR-INSEAN outdoor maneuvering basin. The present work further broadens the results focused on the quasi-steady conditions (straight ahead motion and steady turning) analyzed in Part I (Ortolani et al., 2015 ) to transient maneuvers. After the rudder actuation (both at the start of the turning circle and the pull-out phase), peaks 100% higher than the stabilized value have been highlighted, in particular on the internal shaft. To inspect this aspect in depth, the inertial contribution of the propeller mass is reconstructed by the measurement of the 6DoF motion of the model and is removed from the measured force in order to obtain the hydrodynamic force exerted by the propeller. In addition to the turning circles, ±10°, ±20° and±35° zig–zag maneuvers at three different speeds ( F N = 0.26, 0.32, 0.36 ) were carried out in order to consider the transient effects on the propulsion system during fully unsteady maneuvers. The paper is presented following the same phenomenological style adopted in the previous work in order to clarify the nature of the bearing radial force during transient phases. Abstract : Highlights: Transient behavior propeller radial force. Systematic analysis by free running model tests on a twin screw model. Phenomenological inspection by cross-correlation with the motions of the model. Differences of the features on the two propellers are stressed.